Comparative efficiency analysis of bank branches - Cape Verdean bank - Santos, Gabriela Maria de Figueiredo dos (2022)
Data Envelopment Analysis (DEA) is a mathematical programming-based approach that evaluates the relative efficiency of a set of DMUs (Decision-Making Units) where the conversion of multiple inputs into multiples outputs complicates the comparison of the DMUs performances. A DMU is considered efficient if it belongs to the efficiency frontier created by the performance evaluation of all the DMUs in the set we are evaluating. Portela (2003) developed a model to evaluate bank branches’ efficiency that consid- ered the influence and/or consequences of the new alternative distribution channels for banking transactions. This model divides Bank Branche’s efficiency into three viewpoints: transactional efficiency, operational efficiency, and profit efficiency. Based on this work we will adapt this perspective to a Bank in Cape Verde. Considering Cape Verde’s reality, the Bank showed a lot of interest in the transactional efficiency because they haven’t been able to explore it as well as they wished. We will evaluate the Bank Branches of a Cape Verdean Bank considering two perspectives: transactional efficiency and operational efficiency. To do so we will use DEA models. The goal on the transactional perspective is to assess the branch’s capacity to redirect branch transactions to alternative channels, i.e., assess the performance of bank branches in encouraging the use of alternative means by its customers. To do this analysis we are going to use the BCC model and a Geometric Distance Function. The operational measure of efficiency translates all types of operations that go in a bank branch considering the Bank goals. In this perspective, we had to deal with negative data. To do this analysis we are going to use the Range Directional Model (RDM), the Modified Slacks Based Model (MSBM), and a modified version of the Modified Slacks Based Model(MSBM). Results show that most bank branches are efficient in both perspectives.